Compliance of the Criminal Legislation of Ukraine with the UN Protocol on Firearms - Khavroniuk, Mykola I.; Krasnytskyi, Ivan V.; Lashchuk, Nataliya R. (International Journal of Criminology and Sociology, 2022)
Problems with regulating the trafficking of weapons and ammunition emerged in Ukraine after the collapse of the Soviet Union. The Soviet military left behind a large number of small arms, light weapons and ammunition, much of which did not have proper (in some cases any whatsoever) inventory control and accounting. The purpose of the study is to find the best models of criminal liability for illicit manufacturing and trafficking of firearms in Ukraine, its parts and components and ammunition, taking into account international experience. The study investigates the issue of compliance of the criminal legislation of Ukraine with the United Nations Protocol against the Illicit Manufacturing of and Trafficking in Firearms, Their Parts and Components and Ammunition, supplementing the United Nations Convention against Transnational Organised Crime, and proposes for harmonisation of national legislation with this Protocol. It is concluded that Ukraine needs to adopt the Law "On Arms Trafficking", which, among other things, must clearly define such concepts as "firearms", "parts and components", "ammunition", "illicit manufacturing", "illicit trafficking", etc. which would also be relevant for the criminal legislation of Ukraine.